Analisis Keuntungan Usaha Ternak Ayam Ras Pedaging (Broiler) Pola Mandiri di Kota Sorong - Ivonne Leiwakabessy; Denny Petta; Aprilyana Nice Pongkarambe (Universitas Muhammadiyah Sorong, 2023)
ABSTRACT: One of the livestock commodities that has a fairly high potential to be developed in Indonesia is broilers, because in addition to being easy to maintain, the meat is also much loved by the public. The purpose of this study is to analyze how much profit broiler or broiler farmers make in Sorong City. The method used in this research is a case study method, which is research carried out by looking directly at the field. The sampling method uses the Purposive sampling method with a total of 10 respondents. The analysis used in this study is the analysis of farming. The results showed that an independent broiler chicken farm in Sorong City made a profit, with an R / C ratio of 1.18, the broiler farming business in Sorong City is worthy of development or worthy of effort